2011
DOI: 10.1128/jvi.02268-10
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus NS2 Coordinates Virus Particle Assembly through Physical Interactions with the E1-E2 Glycoprotein and NS3-NS4A Enzyme Complexes

Abstract: The hepatitis C virus (HCV) NS2 protein is essential for particle assembly, but its function in this process is unknown. We previously identified critical genetic interactions between NS2 and the viral E1-E2 glycoprotein and NS3-NS4A enzyme complexes. Based on these data, we hypothesized that interactions between these viral proteins are essential for HCV particle assembly. To identify interaction partners of NS2, we developed methods to site-specifically biotinylate NS2 in vivo and affinity capture NS2-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
132
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(147 citation statements)
references
References 75 publications
13
132
1
1
Order By: Relevance
“…One well-characterized ion channel-independent p7 function is its interaction with NS2, targeting the latter to defined loci within infected cells where it is thought to act as a 'particle assembly scaffold' (Boson et al, 2011;Jirasko et al, 2008Jirasko et al, , 2010Ma et al, 2011;Popescu et al, 2011;Stapleford & Lindenbach, 2011;Tedbury et al, 2011). p7 and NS2 in concert control sub/genotypedependent compartmentalization of HCV core protein between the ER and lipid droplets, with more efficient particle production resulting from ER-associated core (Boson et al, 2011).…”
Section: Hcv P7mentioning
confidence: 99%
“…One well-characterized ion channel-independent p7 function is its interaction with NS2, targeting the latter to defined loci within infected cells where it is thought to act as a 'particle assembly scaffold' (Boson et al, 2011;Jirasko et al, 2008Jirasko et al, , 2010Ma et al, 2011;Popescu et al, 2011;Stapleford & Lindenbach, 2011;Tedbury et al, 2011). p7 and NS2 in concert control sub/genotypedependent compartmentalization of HCV core protein between the ER and lipid droplets, with more efficient particle production resulting from ER-associated core (Boson et al, 2011).…”
Section: Hcv P7mentioning
confidence: 99%
“…It was suggested that NS5A is responsible for recruiting a replication complex to the vicinity of the LD since the localization of other nonstructural proteins in close proximity of LD depended on the localization of NS5A to LD (19). Several independent studies, including ours, showed that NS2 is involved in virus particle assembly by interacting with both the structural proteins E1 and E2 and also the nonstructural proteins NS3 and NS5A (25)(26)(27)(28). Interestingly, these NS2-mediated interactions are associated with colocalization of E1, E2, NS2, NS3, and NS5A at dot-like structures near LD, and the relative percentages of HCV replicating cells exhibiting these dot-like structures positively correlated with the infectious virus titer (25,26,28).…”
mentioning
confidence: 99%
“…The E1 and E2 envelope proteins are incorporated into ER membranes with ectodomains facing the ER lumen (9, 10). Later, they are recruited to assembly sites via the NS2 complex (11,12). Upon recruitment of all required viral components, HCV assembly is thought to occur at the surface of LDs (6-8, 13).…”
mentioning
confidence: 99%